Applying the behavior change wheel to identify pandemic-related attitudes and feelings about physical activity as predictors of physical activity level among university students in Indonesia during the COVID-19 pandemic - Wibowo, Rakhmat Ari; Sofyana, Meida; Agustiningsih, Denny (Frontiers in Education, 2022)
A recent systematic review found a significant drop in physical activity among university students during the COVID-19 pandemic. Identifying students' attitudes and feelings about physical activity and coronavirus, which could facilitate or hinder physical activity, is essential to guide intervention planning. We conducted a cross-sectional study among university students in Indonesia to collect their physical activity level and their attitudes and feelings about physical activity in pandemic situations. A binomial logistic regression has been conducted to predict whether students will sufficiently engage in physical activity based on their attitudes and feelings related to physical activity and coronavirus and demographic characteristics. Students' perceived health benefits of physical activitu and feeling guilty about wanting to do PA during the pandemic, BMI, and field of study were statistically significant predictors. An increase of one unit of perceived health benefits of PA increases the odds of meeting the PA guidelines by 2.31. On the other hand, rising one point of feeling guilty about conducting physical activity was associated with 1.28 times lower odds of meeting the physical activity guidelines. Thus, intervention should increase students' awareness of the physical health benefits of physical activity during the pandemic and reduce their feeling of guilty about conducting physical activity.